A Twenty-Year Survey in Low-Valent Cobalt-Catalyzed Transformations Comes to an End – A Farewell - Hilt, Gerhard (Synlett, 2022)
In this Account, I report the start of my independent career, concerning cobalt-catalyzed carbon–carbon bond formations and the twenty-year long journey to the final decision to abandon the field. Some highlights, such as the regiodiverse neutral Diels–Alder reaction and the cobalt versus ruthenium-catalyzed Alder-ene reaction are discussed. Besides such highlights, also some aspects that led to unpleasant experiences are reported from a personal point of view.1 Introduction2 The Regiodivergent Neutral-Diels–Alder Reaction3 The Chemoselective [2+2+2] Cyclotrimerization of Alkynes and Nitriles4 The Cobalt-Catalyzed Alder-ene Reaction5 The Isomerization of Carbon–Carbon Double Bonds6 The Final Chord7 Conclusion
Keywords: Alder-ene reaction; catalysis; cobalt; cyclotrimerization; Diels–Alder reaction; hydrovinylation; isomerization